Family Medicine, Primary Care and Violence: Training and action in Iberoamerica - Anderson, Maria Inez Padula (2018)
Objective: To identify the perception of family and community doctors - as well as other professionals in 20 countries that make up the Ibero-American Confederation of Family Medicine (CIMF) - on the most prevalent forms of violence in their country and in the communities they attend. Also, to identify the perception about their own motivation and ability, as well as that of family physicians from their countries, to address violence and contribute to the culture of peace. Methods: Cross-sectional, exploratory study, descriptive and quantitative approach, carried out in the 20 member countries of CIMF, between the months of September 2017 to March 2018. A survey was designed based on a literature review of the study phenomenon, discussion and validation with different family medicine professionals considered to be experts in the subject. It was disseminated with the support of the different scientific societies of Family Medicine that make up the 20 countries of the CIMF, reaching 242 responses. Results: More than 92% of professionals consider that they lack sufficient training to deal with violence in their daily work and only 24% consider that they have received sufficient training in the Culture of Peace. On the other hand, the perception of prevalence of the different types of violence from the personal, family and community point of view in the region is alarming. Conclusions: It is necessary to integrate in the training of family doctors and primary care professionals, as well as in the undergraduate curricula of Medicine, contents related to the approach to violence and the contribution to the culture of peace to overcome violence. The knowledge gap on these issues is visible by family doctors and other professionals who work in Primary Care. On the other hand, the potential benefit of having these professionals acting in this serious and prevalent health problem is remarkable, especially considering their frequent and longitudinal contact with people, families and communities who have been victims of violence.